Evaluation of Corn Stalk as a Substrate to Cultivate King Oyster Mushroom (Pleurotus eryngii) - Yuanyuan Zhou; Zihao Li; Congtao Xu; Jinlong Pan; Haijun Zhang; Qingxiu Hu; Yajie Zou (Horticulturae, 2023)
Corn is widely planted in China, but corn stalks have not been adequately utilized for a long time. Here, the potential of corn stalks to serve as an ingredient in the composition of substrates to cultivate king oyster mushroom (Pleurotus eryngii) was studied. Corn stalks were added to the matrix at a ratio of 10.5%, 21%, or 42% to replace sawdust or sugarcane bagasse in the typical matrix. Analysis of the mycelia growth rate, production days, agronomic traits, and nutrient content confirmed the feasibility of using corn stalk instead of sawdust and bagasse for the cultivation of P. eryngii. The samples grown on Y5 (without sawdust and bagasse) has more crude fiber (8.3%) and polysaccharide (5.05%) content compared to those of the control substrate (7.1% and 4.16%, respectively), moreover, it also conteined more zinc and calcium than others. Therefore, these findings indicate that corn stalks could be used as an alternative to sawdust and sugarcane bagasse for P. eryngii production, which would not only reduce costs and improve food quality, but also improve waste utilisation.